2011
DOI: 10.17159/2078-516x/2011/v23i2a343
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for chronic low back pain: whole body vibration and spinal stabilisation

Abstract: A range of exercise modalities is used in the rehabilitation of individuals with chronic lower back pain (CLBP), the most current being whole body vibration (WBV) training. WBV training is a novel neuromuscular mode of exercise that has recently received awareness as both a medium for improving speed-strength performance in elite athletes, but also as an alternative or complementary training modality to existing exercise programmes in most biokinetics practices and health and fitness centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The vibrations also activate the supplementary motor area, the Caudal cingulate motor area, and the 4 th brain region, which may affect the excitation level of peripheral and central structures of the brain to facilitate subsequent voluntary movements (39). Our results support those of Baard et al study, in that, they found whole-body vibration exercises significantly improved back muscles endurance over the stabilization exercises (40). Vibration waves stimulate the primary ending of the muscle spindles and activate a large portion of the motor neuron in the neural pool, as a result, contract motor units that were previously inactive.…”
Section: Discussionsupporting
confidence: 87%
“…The vibrations also activate the supplementary motor area, the Caudal cingulate motor area, and the 4 th brain region, which may affect the excitation level of peripheral and central structures of the brain to facilitate subsequent voluntary movements (39). Our results support those of Baard et al study, in that, they found whole-body vibration exercises significantly improved back muscles endurance over the stabilization exercises (40). Vibration waves stimulate the primary ending of the muscle spindles and activate a large portion of the motor neuron in the neural pool, as a result, contract motor units that were previously inactive.…”
Section: Discussionsupporting
confidence: 87%
“…No statistical difference was found between groups for LBP as measured by the VAS. Core exercise training with/without WBV has been used as a means to treat participants with chronic LBP [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 42 ]. To the authors knowledge this is the first study that has used WBV to prevent or reduce LBP in otherwise healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of core muscle training programs have been used to successfully reduce chronic LBP [ 9 ]. More recently, whole body vibration (WBV) training has been used to reduce LBP and overall disability in patients with chronic LBP [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. WBV is a low frequency, low amplitude, mechanical vibration exercise that has been shown to induce muscular contractions and influence neuromuscular potentiation through the tonic vibration reflex [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBV exercise has been shown to improve muscle performance and strength [27,28]. Several studies have reported an increase in the endurances of abdominal and multifidus muscles in CLBP patients following WBV exercise [29,30]. The activation of a larger fraction of the motor neuron pool and the recruitment of previously inactive motor units into contraction results in more efficient use of the force production potential [29,30]; this is considered to be the major effect of vibration exercise.…”
Section: Discussionmentioning
confidence: 99%